Effect of CuO Loading on the Photocatalytic Activity of SrTiO3 for Hydrogen Evolution - Xuan Truong Mai; Duc Nguyen Bui; Van Khang Pham; Thi Hien Lan Nguyen; Thi To Loan Nguyen; Hung Dung Chau; Thi Kim Ngan Tran (Inorganics, 2022)
A CuO-loaded SrTiO3 catalyst showed highly photocatalytic activity for H2 evolution. This catalyst was prepared by an impregnation method and characterized by XRD, TEM, BET, XPS, Uv-vis DRS and PL techniques. Under optimum conditions, the best rate of H2 evolution of the CuO-loaded SrTiO3 catalyst is 5811 µmol h−1g−1, whereas it is a mere 34 µmol h−1g−1 for the pure SrTiO3. High efficiency, low cost and good stability are some of the merits that underline the promising potential of CuO-loaded SrTiO3 in the photocatalytic hydrogen.